FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empirik Pada Perusahaan Yang Terdaftar Di BEI Periode 2017-2019) - Dita Ayu Lestari (2021)
This study uses quantitative methods that aim to examine the relationship between consumer proximity, environmental performance, profitability, and media exposure on corporate social responsibility disclosure. This study uses data from companies listed in Indonesia Stock Exchange (IDX) 2017-2019. Sampling uses a purposive sampling method with 60 samples on the Indonesia Stock Exchange (IDX). Testing of hypothesis in this study using multiple linear regression with software SPSS. The results of this study are consumer proximity has a positive effect on the corporate social responsibility disclosure. Environmental performance, profitability, media exposure has no effect on corporate social responsibility disclosure.